'Forgotten Europeans': transnational minority activism in the age of European integration. Issue 2 (15th February 2018) - Smith, David J.; Germane, Marina; Housden, Martyn
Abstract: This article examines transnational activism by coalitions of national minorities in Europe from the early 20th century to the present, setting this within the broader 'security versus democracy dilemma' that continues to surround international discussions on minority rights. Specifically, we analyse two organisations – the European Nationalities Congress (1925–1938) and the Federal Union of European Nationalities (1949–) – which, while linked, have never been subject to a detailed comparison based on primary sources. In so far as comparisons do exist, they present these bodies in highly negative terms, as mere fronts for inherently particularistic nationalisms that threaten political stability, state integrity and peace. Our more in‐depth analysis provides a fresh and more nuanced perspective: it shows that, in both cases, concepts of European integration and 'unity in diversity' have provided the motivating goals and frameworks for transnational movements advocating common rights for all minorities and seeking positive interaction with the interstate world.